Concentrations of plasma estradiol, progesterone, melatonin, serotonin and nitric oxide in Tuj ewes after estrus syncronization in and out of breeding season - Okulmus, C; Atakisi, E (Journal of the Hellenic Veterinary Medical Society, 2024)
This study aimed to determine and compare the concentrations of progesterone, estradiol, melatonin, serotonin and nitric oxide in the blood plasma following induced estrus in (autumn) and outside (spring) the natural breeding season in ewes. In addition, seasonal changes in serotonin levels following induced estrus in ewes were examined for the first time. A total of 20 Tuj ewes were used in the study. The ewes were synchronized in the breeding season (n=10) and non-breeding season (n=10) by using an intravaginal progestin-containing sponge (60 mg medroxy-progesterone acetate) for 12 days. Then, the sponge was withdrawn, and 2.5 mL of prostaglandin F2 alpha (PGF2α) was injected intramuscularly with 500 IU pregnant mare serum gonadotrophin (PMSG). The first blood samples were collected immediately after removal of the intravaginal sponge (at 0 hour) and the rest was collected at 4-hour intervals between 24 and 68 hours. Throughout both seasons, all animals displayed estrus. However, estrus appeared sooner and was more intense in the breeding season than in the non-breeding season. Plasma concentrations of progesterone (respectively; 0.65±0.36 vs. 0.47±0.20 ng/mL, P < 0.05), estradiol (respectively; 35.42±26.66 vs. 28.36±19.86 ng/L, P < 0.05), nitric oxide (respectively 15.01±2.32 vs. 14.41±2.74 µmol/L, P < 0.05) and melatonin (respectively; 118.76 ±35.5 vs. 93.03±44.34 ng/L, P < 0.05) were higher in the breeding season and a positive correlation was recorded between estradiol and changes in progesterone (r=0.685; P < 0.05) and nitric oxide (r=0.535; P < 0.05). However, the plasma serotonin concentrations (respectively; 66.16 ±21.93 vs. 50.79±29.18 ng/mL, P < 0.05) were higher in the non-breeding season and showed a positive correlation with melatonin (r=0.671; P < 0.05). In addition, significant differences were noted between day and night concentration changes in melatonin and serotonin hormones in both seasons (P < 0.05). In conclusion, the results show seasonal differences in the secretion of ovarian steroid hormones and nitric oxide following induced estrus, which suggests a different reproduction capacity in the two seasons. Seasonal differences in the profile of nitric oxide release during estrus are likely related to estradiol secretion. The study shows that changes in melatonin and serotonin concentrations and circadian differences in their release in and out the breeding season are not affected by estrus synchronization.